Loss of Agricultural Lexis in Cakap Karo - Inggrid Gibretta Khairani Ginting; Rahmad Husein (LINGUISTIK TERAPAN, 2016)
This qualitative research deals with a study on the lexical loss, which is aimed at (1) investigating the level of agricultural lexical loss, (2) describing the patterns of agricultural lexical loss, (3) explaining the reasons of agricultural lexical loss in Cakap Karo. This research has drawn the following conclusions. Firstly, the level of agricultural lexical loss ofCakap Karo among hard plants, plants for food, herbs plant and kinds of flower categories were occured in fourth level (not know and not use) which had different percentages. The highest level of agricultural lexical loss in Cakap Karo occurred in kinds of flower category and the lowest level occurred in plants for food category. Secondly, the agricultural lexical loss was proportionally patterned into potential and total lexical loss. There were 103 (one hundred and three) potential agricultural lexical loss and 146 (one hundred forty six) total agricultural lexical loss. Thirdly, the reasons of agricultural lexical loss in Cakap Karo were linguistics, prestige and technology factors. Keywords: language loss, agricultural lexis, Cakap Karo